2016
DOI: 10.4236/ojfd.2016.63013
|View full text |Cite
|
Sign up to set email alerts
|

Joule Heating and Viscous Dissipation on Effects on MHD Flow over a Stretching Porous Sheet Subjected to Power Law Heat Flux in Presence of Heat Source

Abstract: In the present work we investigate the effects of Joule heating and viscous dissipation on MHD fluid flow. The viscous incompressible fluid flows over a stretching porous horizontal sheet subjected to power law heat flux in presence of heat source. The equations of momentum and heat transfer governing the problem are transformed into a system of dimensionless differential equations, which in turn solved numerically using shooting technique. The effects of the Joule heating parameter, permeability parameter, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Azimi et al analytically discussed MHD flow of viscous fluid through Stretching sheet using DTM-pade approach to solve boundary layer equations of given flow problem [21]. Jabar addressed the influence of viscous dissipation and joule heating on MHD flow through a stratified sheet subjected to power Law Heat Flux having heat source [22]. Reddy discussed unsteady MHD transport of rotating fluid past a permeable surface confined by infinite vertical permeable plate and concluded that by increasing rotating parameter the velocity field is also increased [23].…”
Section: Introductionmentioning
confidence: 99%
“…Azimi et al analytically discussed MHD flow of viscous fluid through Stretching sheet using DTM-pade approach to solve boundary layer equations of given flow problem [21]. Jabar addressed the influence of viscous dissipation and joule heating on MHD flow through a stratified sheet subjected to power Law Heat Flux having heat source [22]. Reddy discussed unsteady MHD transport of rotating fluid past a permeable surface confined by infinite vertical permeable plate and concluded that by increasing rotating parameter the velocity field is also increased [23].…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of Joule and viscous heating effects on 3D hydromagnetic flow including mass and heat fluxes were examined by Muhammad et al [24]. Jaber [25] investigated the power law heat flux with Joule heating and viscous dissipation on 3D hydromagnetic through a porous stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Gideon et al studied the effect of viscous dissipation effect on the mixed convection MHD flow towards a stagnation point with convective boundary condition in porous media. Jabber studied the effect of viscous dissipation on flow over a stretching porous sheet subjected to power law heat flux in presence of heat source. The study of MHD‐free convective fluid in present of viscous dissipation and chemical reaction in a slip dominant region is made by Sengupta and Ahmed…”
Section: Introductionmentioning
confidence: 99%
“…Sengupta and Ahmed obtain closed‐form solutions for the MHD‐free convective mass transfer flow of radiative uniform heat generation (absorption) fluid through a wavy permeable channel in presence of Soret and Dufour effects. The Joule heating and viscous dissipation effects on MHD flow over a stretching porous sheet subjected to power law heat flux were studied by Jaber . Srinivasa and Eswara studied the effects of internal heat generation or absorption on MHD‐free convection flow from an isothermal truncated cone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation